Analysis of the Requirements for Digital Teaching Materials in Appreciation and Indonesian Literary Criticism Subject in State University of Medan - Fitriani Lubis; Salmah Naelofaria; Rumasi Simare-mare (Britain International for Academic Research (BIAR) Publisher, 2020)
Entering industrial revolution 4.0 and society 5.0 era, teacher and candidate teacher preparation to be a professional should better through the increasing of competency that fit in 21st century. Indonesian Languange and Literature Education Study Program in State University of Medan as an institution that produce future candidate educator for Indonesian languange and literature has a great responsibilities to produce a teacher who have adequate 21st century’s competency. The needs analysis is an initial study for research in digital teaching materials development of Appreciation and Indonesian Literary Criticism Subject in State University of Medan. The aim of this research is to look the extent of the level of need of the academic community in Indonesian Languange and Literature Education Study Program for the development of digital teaching materials. This research use descriptive method. Data are collected by observation, interview, and questionnaire. This study is a descriptive research with survey method that held between August and September 2019 in Indonesian Languange and Literature Education Study Program in State University of Medan. The population is all third-semester students in this study program that take Appreciation and Indonesian Literary Criticism Subject with 124 students. The sampel is selected randomly by 75 students. Futhermore, the questionnaire is also given to this study program lecturers that count 28 lecturers to know the illustration of teaching process that do based on academic community’s requirements in this study program towards the high of digital teaching materials development. The findings of this study show that the academic community’s requirements for the development of digital-based teaching materials in this study program is high. Students who are the sample hope that the teaching materials of that subject could be develop to be based on digital and could be access all the time by all students.